2019
DOI: 10.3892/ol.2019.10298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melanoma differentiation associated gene-7 (MDA-7/IL-24) on apoptosis of liver cancer cells via regulating the expression of B-cell lymphoma-2

Abstract: The present study investigated the mechanism of selective killing of liver cancer cells of melanoma differentiation associated gene-7 (MDA-7, also called IL-24α) in order to provide a theoretical basis for gene therapy of liver cancer. A recombinant eukaryotic expression vector (pcDNA3-MDA-7) containing human MDA-7 gene was constructed, which was then delivered to liver cancer cell line HepG2 and normal liver cell line L02. The positive cell clone was screened by G418. Reverse transcription quantitative polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, we analyzed the Kaplan–Meier curves in HNSCC and each subgroup, all of which suggested that IL24 mRNA expression had no significant correlations with the status of prognosis, which needs to be verified with more cohorts. IL24 can protect the body via the induction of tumor cell apoptosis and inhibition of angiogenesis [ 10 , 11 ] in cancers such as colorectal adenocarcinoma and hepatic carcinoma [ 34 , 35 ]. IL24 has also been found in many diseases involving inflammation, such as cardiovascular disease, rheumatoid arthritis, tuberculosis , and viral infections, and may play a role in psoriasis [ 15 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we analyzed the Kaplan–Meier curves in HNSCC and each subgroup, all of which suggested that IL24 mRNA expression had no significant correlations with the status of prognosis, which needs to be verified with more cohorts. IL24 can protect the body via the induction of tumor cell apoptosis and inhibition of angiogenesis [ 10 , 11 ] in cancers such as colorectal adenocarcinoma and hepatic carcinoma [ 34 , 35 ]. IL24 has also been found in many diseases involving inflammation, such as cardiovascular disease, rheumatoid arthritis, tuberculosis , and viral infections, and may play a role in psoriasis [ 15 , 36 ].…”
Section: Discussionmentioning
confidence: 99%